Does prenatal methamphetamine exposure induce sensitization to drugs in adulthood? - Macúchová, E; Šlamberová, R (Physiological research, 2017)
Behavioral sensitization is defined as augmented psychomotor activity, which can be observed after drug re-administration following withdrawal of repeated drug exposure. It has been shown that abuse of one drug can lead to increased sensitivity to certain other drugs. This effect of developed general drug sensitivity is called cross-sensitization and has been reported between drugs with similar as well as different mechanisms of action. There is growing evidence that exposure to drugs in utero not only causes birth defects and delays in infant development, but also impairs the neural reward pathways, in the brains of developing offspring, in such a way that it can increase the tendency for drug addiction later in life. This review summarizes the results of preclinical studies that focused on testing behavioral cross-sensitization, after prenatal Methamphetamine exposure, to drugs administered in adulthood, with both similar and different mechanisms of action. Traditionally, behavioral sensitization has been examined using the Open field or the Laboras Test to record locomotor activity, and the Conditioned Place Preference and Self-administration test to examine drug-seeking behavior. However, it seems that prenatal drug exposure can sensitize animals not only to the locomotor-stimulating and conditioning effects of drugs, but may also be responsible for modified responses to various drug effects.
Keywords: těhotenství; Central Nervous System Stimulants; modely u zvířat; Substance-Related Disorders; ženské pohlaví; Locomotion; zvířata; poruchy spojené s užíváním psychoaktivních látek; Humans; methamfetamin; Pregnancy; zpožděný efekt prenatální expozice; stimulanty centrálního nervového systému; Methamphetamine; Female; lokomoce; Prenatal Exposure Delayed Effects; Models, Animal; lidé; Animals